Decoding antibiotic resistance in Pseudomonas aeruginosa: Embracing innovative therapies beyond conventional antibiotics - Nomita Gupta; Kanchan Chauhan; Garima Singh; Shobhi Chaudhary; Jitendra Singh Rathore (The Microbe)
Pseudomonas aeruginosa, an important Gram-negative opportunistic pathogen, is accountable for numerous acute and chronic infections, resulting in mortality rates of up to 40 % and significant morbidity. This opportunistic bacterial pathogen targets individuals with conditions like cystic fibrosis, burn wounds, chronic obstructive pulmonary disorder (COPD), immunodeficiency, cancer, and those experiencing severe infections requiring ventilation, such as in the case of COVID-19. Treatment with antibiotics is currently the only means of preventing P. aeruginosa infections. The pathogens acquired and adaptive mechanisms have led to a rise in the prevalence of multidrug-resistance, which poses a significant challenge in healthcare environments. The bacterial pathogen uses many strategies such as the formation of biofilms, multidrug resistance, and antibiotic tolerance, to spread and maintain infection. The mechanisms of intrinsic and adaptive resistance utilized by this microbe to empower its pathogenesis are covered in great detail in this review. The different antibiotics that are employed in clinical settings to treat P. aeruginosa infections are also discussed. Furthermore, various therapeutic strategies to treat P. aeruginosa infections such as phage therapy and CRISPR-Cas9, antimicrobial peptides, immunomodulators, use of nanotechnology, vaccine development, and the revolutionary concept of drug repurposing are well discussed. Coherently, we draw attention to the research on alternative as well as innovative methods to control P. aeruginosa infections replacing the need of traditionally available antibiotics.